Relationship between Nutrition Knowledge, Family Income, and Consumption Pattern with the Incidence of Chronic Energy Deficiency in Pregnant Women - Nurhamidi, Nurhamidi; Rifqa, Magfirah Annisa (Journal of Local Therapy, 2022)
Abstract: Background: Indirect factors that play an important role in complications in pregnant women, one of which is chronic energy deficiency (CED) caused by insufficient energy and protein intake in pregnant women. In 2020 the number of cases of CED in pregnant women at the Birayang Health Center has increased to 14.56%. The incidence of CED can occur because of low knowledge about nutrition, low family income, and fewer consumption patterns. Objective: To determine the relationship between nutritional knowledge, family income, and consumption patterns with the incidence of chronic energy deficiency (CED) in pregnant women in the work area of the Birayang Health Center, Central Hulu Sungai Regency. Methods: This type of research used observational analytics with a cross-sectional study design. Results: Respondents who experienced CED were 31.25% and those who did not experience CED were 68.75%. Respondents with good nutrition knowledge were 66.7%, adequate nutrition knowledge was 27.1% and 6.2% lacked nutrition knowledge. Family income in the high category is 29.2% and in the low category is 70.8%. Consumption patterns in the good category were 45.8% and the less category was 54.2%. Results: There is a relationship between nutritional knowledge, family income, and consumption patterns with the incidence of CED in pregnant women.